The accession of the EU to the European Convention on Human Rights: a critical analysis of the Opinion of the European Court of Justice - Nergelius, Joakim (Stockholm, 2015)
"The Lisbon Treaty clearly expresses that the EU should accede to the European Convention on Human Rights and Fundamental Freedoms (ECHR). Nonetheless, the Court of Justice ruled, quite unexpectedly, in December 2014, that the draft agreement on the accession is not compatible with EU law. In this report, the author sheds light on the Court’s opinion and addresses the question of what happens now."